Regulatory T Cell Immunity in Atherosclerosis - Hilman Zulkifli Amin; Naoto Sasaki; Ken-Ichi Hirata (Acta Medica Indonesiana)
Atherosclerosis is a chronic inflammatory disorder involving innate and adaptive immunity process. Effector T cell (Teff) responses promote atherosclerotic disease, whereas regulatory T cells (Tregs) have been shown to play a protective role against atherosclerosis by down-regulating inflammatory responses which include multiple mechanisms. Compelling experimental data suggest that shifting the Treg/Teff balance toward Tregs may be a possible therapeutic approach for atherosclerotic disease, although the role of Tregs in human atherosclerotic disease has not been fully elucidated. In this review, we discuss recent advances in our understanding of the roles of Tregs and Teffs in experimental atherosclerosis, as well as human coronary artery disease.